Revised Masses for Low-density Planets Orbiting the Disordered M-dwarf System TOI-1266 - Dakotah Tyler; Erik A. Petigura; James Rogers; Jack Lubin; Andreas Seifhart; Jacob L. Bean; Madison Brady; Rafael Luque (The Astronomical Journal)
We present an analysis of 126 new radial velocity measurements from the MAROON-X spectrograph to investigate the TOI-1266 system, which hosts two known transiting sub-Neptunes at 10.8 and 18.8 days. We integrated our measurements with existing HARPS-N measurements for this system and derived revised masses for TOI-1266 b and c of M _b = 4.09 ± 0.45 M _⊕ and M _c = 2.64 ± 0.52 M _⊕ , respectively. The Keplerian fit from the combined datasets enabled an ≈35% and ≈41% improvement in mass precision for planet b and c, respectively, compared to the previously published values. With bulk densities of ρ _b = 1.25 ± 0.21 g cm ^−3 and ρ _c = 1.51 ± 0.39 g cm ^−3 , the planets are among the lowest density sub-Neptunes orbiting an M dwarf. They are both consistent with rocky cores surrounded by hydrogen helium envelopes. TOI-1266 c may also be consistent with a water-rich composition, but we disfavor that interpretation from an Occam's razor perspective.